2013
DOI: 10.1007/s12471-013-0407-x
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of guidelines for implantable cardioverter-defibrillator therapy in clinical practice: Which patients do benefit?

Abstract: PurposeBased on multiple large clinical trials conducted over the last decades guidelines for implantable cardioverter-defibrillator (ICD) implantations have been evolving. The increase in primary prophylactic ICD implantations challenges us to be critical towards the indications in certain patient populations.MethodsWe retrospectively collected patient characteristics and rates of appropriate and inappropriate ICD therapy, appropriate and inappropriate ICD shock and mortality of all patients who received an I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 50 publications
2
25
0
2
Order By: Relevance
“…Patients who are at high risk for life‐threatening ventricular arrhythmias are preferably treated with an implantable cardioverter defibrillator (ICD). The number of ICD patients has increased due to expanding indications, leading to higher workload and increased healthcare costs . Remote patient monitoring (RPM) systems can send disease‐ and ICD‐related data from the patient's home to the hospital, and are, therefore, a promising alternative to in‐clinic follow‐up …”
Section: Introductionmentioning
confidence: 99%
“…Patients who are at high risk for life‐threatening ventricular arrhythmias are preferably treated with an implantable cardioverter defibrillator (ICD). The number of ICD patients has increased due to expanding indications, leading to higher workload and increased healthcare costs . Remote patient monitoring (RPM) systems can send disease‐ and ICD‐related data from the patient's home to the hospital, and are, therefore, a promising alternative to in‐clinic follow‐up …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown male sex as an independent risk factor for appropriate ICD therapies 438 . Women are 30%‐50% less likely to receive an appropriate shock, 439–442 and this difference is more pronounced among CRT‐D recipients 443–445 . However, most of studies have shown similar mortality rates in both genders after ICD implantation 438–445 .…”
Section: How To Assess Risk For Adverse Outcomes In Patients With Venmentioning
confidence: 99%
“…Given the growth in the number of patients receiving a cardiovascular implantable electronic device (CIED), in particular the implantable cardioverter defibrillator (ICD) and cardiac resynchronisation therapy (CRT) devices, the burden on outpatient clinics to follow up these patients is increasing [ 1 – 3 ]. Remote patient monitoring offers a potential solution to this problem [ 4 ].…”
Section: Introductionmentioning
confidence: 99%